IMPACT OF COVID-19 PANDEMIC ON STILLBIRTH RATES IN DEVELOPING COUNTRIES: A STUDY FROM LADY READING HOSPITAL, PAKISTAN - YASMIN , S; SYED , W; SALEEM , A; FARID , W; NASEEM , S (Biological and Clinical Sciences Research Journal, 2023)
The COVID-19 pandemic has created challenges, particularly for underdeveloped countries with fragile healthcare systems. These nations are experiencing increased pressure due to the pandemic and ongoing illnesses. This research aims to evaluate how the pandemic has indirectly impacted mother and newborn health in Pakistan, resulting in higher stillbirth rates. The study will analyze data from pre-pandemic and pandemic years to determine how healthcare interruptions, fewer prenatal visits, and infection concerns have affected stillbirth occurrences in tertiary-care hospitals. It is a cross-sectional study conducted at the Department of Obstetrics and Gynecology at Lady Reading Hospital, Peshawar, Pakistan, from January 2019 to January 2020. The Department of Obstetrics and Gynaecology at Lady Reading Hospital in Peshawar, Pakistan, conducted this cross-sectional research. Approved by ethics was acquired. Using internet calculators, the sample size of 200 was determined with a 5% margin of error, a 95% confidence interval, and a stillbirth percentage of 16%. Consecutive non-probability sampling was used. Patients who were at term and gave birth to stillborn children were included in the study; instances involving twin pregnancies, fetal abnormalities, and early neonatal deaths were not. For 2019 (before COVID-19) and 2020 (the pandemic year), retrospective data on medical problems, reasons for stillbirth, demographic traits, and prenatal visits were gathered. The causes of stillbirths were compared between the two years using chi-square testing. A p-value of 0.05 was considered statistically significant. The research discovered notable differences in stillbirth rates and associated variables between 2019 (before COVID-19) and 2020 (the pandemic year). The proportion of multiparous women increased to 62% in 2020 from 57% in 2019. A decline in prenatal bookings from 64% in 2019 to 52% in 2020 suggests that antenatal visits were fewer throughout the epidemic. There were notable variations between the two years in several stillbirth-related factors, including abruption, placenta previa, type II diabetes, gestational diabetes mellitus (GDM), malpresentation, intrauterine growth restriction (IUGR), obstructed labor, eclampsia, postdates, and unknown causes. These results demonstrate how the pandemic affected maternity care and how stillbirth rates are related to it. In an environment with inadequate resources, the research shows a significant rise in stillbirth rates during the COVID-19 epidemic. This increase is attributed to fewer prenatal visits, interruptions in healthcare services, and the pandemic’s collateral consequences. These results highlight the need for tailored treatments and program changes for maternal health during medical emergencies.